Persepsi Generasi Z pada Konten Iklan Sampo Rejoice x Kiky Saputri versi “Rambut No Drama” - Chandra, Vanessa; Utami, Lusia Savitri Setyo (Prologia, 2023)
The increasing number of internet users in Indonesia is used by many companies or brands as an opportunity to market their products through advertisements on social media. One of them is Rejoice shampoo which creates promotional advertising content on YouTube social media. One of the active YouTube users is Generation Z, so it has the potential to be a subject in this study. The purpose of this research is to describe Generation Z perception of Rejoice shampoo creative advertising content on YouTube. Creative advertising content tends to attract the attention of potential consumers more than non-creative ones. The theoretical basis used in this study is marketing communications, advertising, creative advertising, advertising on social media, and perception. This research was conducted with a qualitative approach. Researchers also conducted in-depth interviews with four informants who met the criteria. The perception that appears in Generation Z is divided into three stages, namely sensation, attention, and interpretation. The results of this study indicate that Generation Z perception of the content of the Rejoice x Kiky Saputri shampoo advertisement version of "Rambut No Drama" is that advertisements are creative, interesting, funny, not monotonous, and different from shampoo advertisements in general. Peningkatan jumlah pengguna internet di Indonesia dimanfaatkan banyak perusahaan atau brand sebagai peluang dalam memasarkan produk melalui iklan di media sosial. Salah satunya adalah sampo Rejoice yang membuat konten iklan promosi di media sosial YouTube. Salah satu pengguna aktif YouTube adalah Generasi Z sehingga berpotensi sebagai subjek dalam penelitian ini. Tujuan penelitian ini adalah untuk mendeskripsikan persepsi Generasi Z terhadap konten iklan kreatif sampo Rejoice di YouTube. Konten iklan yang kreatif cenderung lebih menarik perhatian calon konsumen dibandingkan yang tidak kreatif. Landasan teoritis yang digunakan dalam penelitian ini adalah komunikasi pemasaran, periklanan, iklan kreatif, iklan pada media sosial, dan persepsi. Penelitian ini dilakukan dengan pendekatan kualitatif. Peneliti juga melakukan wawancara mendalam kepada empat informan yang telah memenuhi kriteria. Persepsi yang muncul pada Generasi Z ini terbagi menjadi tiga tahapan yaitu sensasi, atensi, dan interpretasi. Hasil dari penelitian ini menunjukkan bahwa persepsi Generasi Z terhadap konten iklan sampo Rejoice x Kiky Saputri versi “Rambut No Drama” adalah iklan yang kreatif, menarik, lucu, tidak monoton, dan berbeda dengan iklan sampo pada umumnya.